Marketing strategy of Saruhan packaged sambal MSME in Bandung, Indonesia: Some notes from Islamic perspective‎ - Ramadhani, Annisa Octaviola; Hasbi, Imanuddin; Suryono, Herdiansyah Gustira Pramudia (Universitas Islam Indonesia, 2025)
IntroductionPackaged sambal has evolved from a traditional Indonesian condiment into a commercially viable product, driven by increasing demand for convenience, authenticity, and cultural identity. Micro, small, and medium enterprises in this sector face intense competition from established brands, resource constraints, and shifting consumer behaviors, particularly among Generation Z. Halal certification and Islamic marketing principles are increasingly recognized as strategic tools for building trust and competitive advantage.ObjectivesThis study examines the marketing strategies of a Bandung-based packaged sambal enterprise, integrating market size analysis, segmentation–targeting–positioning, the marketing mix, and Islamic marketing principles. It aims to assess how these combined strategies influence sales growth, market penetration, customer loyalty, and competitive positioning.MethodA qualitative, single-case study design was applied, using purposive sampling to select internal stakeholders and customers as participants. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using thematic coding in NVivo 12 Plus. The analysis focused on market potential estimation through TAM–SAM–SOM, STP implementation, the 4Ps, and the integration of Islamic marketing practices.ResultsFindings indicate that precise market sizing, a Generation Z-focused STP strategy, a coherent marketing mix, and strong digital-first promotion significantly increased monthly sales over six months. Halal certification reinforced consumer trust, strengthened brand loyalty, and enhanced differentiation. Digital platforms, influencer collaborations, and culturally authentic storytelling proved effective in aligning with consumer values and preferences.ImplicationsThe study provides theoretical support for integrating cultural authenticity, ethical branding, and digital-first strategies in MSME marketing. Practically, it offers a replicable model for small enterprises seeking competitive advantage in culturally rooted food sectors. Policy implications include the need for supportive certification processes and digital literacy programs to empower MSMEs.Originality/NoveltyThis study contributes to the literature by presenting an integrated framework that combines market analysis, consumer behavior alignment, and Islamic marketing principles, demonstrating their synergistic impact on MSME performance in the halal and culturally authentic packaged food market.